Laryngeal leiomyoma: A case report and review of the literature - Gómez-Torres, António; Vallejo, Antonio Medinilla; Bueno, Alicia Menoyo; Luna, Ramón Moreno; Cantón, Joaquín Roberto González (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2013)
Leiomyoma is a benign tumour of the smooth muscle that is most typically located in the feminine genitourinary tract. Laryngeal localisation is very uncommon; only 43 cases have been reported in the world literature yet. Surgical resection is the main treatment and recurrences are extremely infrequent. We hereby present a case of laryngeal leiomyoma, its treatment and literature review.